Evaluation of Damage Degree of Inconel 718 using Nondestructive Indicators of Damage - Krysztofik Józef (Fatigue of Aircraft Structures, 2016)
This paper presents the results of the quantitative evaluation of the degree of damage caused by plastic strain accumulated in static tensile tests and creep tests. To detect changes in the structure of the material and in order to determine the degradation of the materials, nondestructive methods were used, namely the ultrasonic and eddy current methods. In ultrasonic testing, attenuation and acoustic birefringence were used as damage indicators. In the case of the eddy current method, changes in the phase angle of impedance were observed in the material. The material tested was Inconel 718 alloy. Inconel alloys are often find application in extreme working conditions including in the power engineering industry, aviation and aerospace. A new type of specimen with the variable cross-sectional area of the measuring part was used in the tests. This allowed researchers to obtain a continuous distribution of plastic strain and enabled analysis of the material with respect to different damage degrees. The correlation between the degree of damage, expressed by the measure of deformation, and the value of nondestructive indicators was determined. On the basis of it, the dependence indicating the ability to nondestructive evaluation of the degradation degree of the material, subjected to loads exceeding the yield limit was obtained.